Anthropomorphism of god explains behavioural evidence for beliefs in tempting fate in religious persons - Goh, Marcus Tian Xi (Nanyang Technological University, 2023)
People avoid tempting fate because they intuitively believe that it would result in misfortune. Perceiving God as having a humanlike capability to watch and take control can explain these beliefs in tempting fate (BTF)—to tempt fate is to offend God and invite punishment. This study aims to examine whether beliefs of people primed with anthropomorphism of God (AoG) would influence their subsequent behavioural response. We predict that a stronger AoG prime would increase participants’ avoidance of tempting fate, even after controlling for risk taking, religious motivation, faith in intuition, negativity bias, gender, and age, especially among religious participants. In a double-blind experiment manipulating AoG using an image selection priming task, 96 undergraduates from a Singaporean university were randomly assigned to either the strong or weak AoG condition, where they viewed images of humans or objects, respectively. Participants willingness to incur a cost by rejecting limited opportunities to tempt fate for a reward measured their BTF. Using negative binomial regression modelling appropriate for count data, the effect of AoG condition, b ≤ 0.40, was not significant for religious participants, before and after including covariates, ps ≥ .13, failing to support the hypotheses. However, the significant interaction between AoG and religious motivation scores, b = 0.36, p = .048, suggest that among the highly religious, AoG influences BTF. After certain exploratory analyses, we suggest that AoG influences BTF when one perceives the higher power as watchful and punitive, can easily assess these concepts, and believes in the higher power.